Treating infectious diseases in a microbial world : report of two workshops on novel antimicrobial therapeutics (Online access: NCBI NCBI Bookshelf., 2006)
Humans coexist with millions of harmless microorganisms, but emerging diseases, resistance to antibiotics, and the threat of bioterrorism are forcing scientists to look for new ways to confront the microbes that do pose a danger. This report identifies innovative approaches to the development of antimicrobial drugs and vaccines based on a greater understanding of how the human immune system interacts with both good and bad microbes. The report concludes that the development of a single superdrug to fight all infectious agents is unrealistic.